Effectiveness of oral health education on 8- to 10-year-old school children in rural areas of the Magway Region, Myanmar - Kyu Kyu Swe; Aung Kyaw Soe; Saw Htun Aung; Htin Zaw Soe (BMC, 2021)
Abstract Background Oral diseases are common and widespread around the world. The most common oral diseases are preventable, and early onset is reversible. Myanmar faces many challenges in rendering oral health services, because approximately 70% of the total population resides in rural areas. These relate to the availability and accessibility of oral health services. Therefore, oral health education is one key element to prevent oral diseases and to promote oral health. Methods A quasi-experimental study was carried out at Basic Education Middle Schools in rural areas of Magway Township to study the effectiveness of oral health education on the knowledge and behavior of 8- to 10-year-old school children. A total of 220 school children, 110 from intervention schools and 110 from control schools, participated in this study from 2015 to 2017. Data were collected before and after intervention in the two groups by using a self-administered questionnaire. Tooth brushing method data were collected by direct observation with a checklist. Oral health education was provided at eight weekly intervals for 1 year. At one and a half years, third-time data collection was done on the intervention group to assess retention. Chi-square test, two samples t-test and one-way repeated measure ANOVA were used for data analysis. The study was approved by the Institutional Review Board of the University of Public Health in Yangon, Myanmar. Results There were significant differences between the two groups in four out of five knowledge questions (p < 0.05) and all behavior questions (p < 0.001) after intervention. A positive effect of oral health education for a period of 45 min at eight weekly intervals for 1 year was found in the intervention group. The intervention had a significant effect on the sustainability of the correct knowledge and behavior of the intervention group although the education session was stopped for 6 months (p < 0.001). Their mean knowledge and behavioral scores at three different points in time were (2.45 ± 1.12 and1.56 ± 0.90) at baseline, (3.79 ± 1.12 and 3.60 ± 1.21) at 1 year after education and (4.07 ± 0.98 and 3.24 ± 1.31) at 6 months after cessation of education, respectively. Conclusions Repeated oral health education was effective in promoting and sustaining oral health knowledge and behavior.